Boosting Oxygen Reduction Performance of Manganese Oxide in Alkaline Media by Three-Dimensional Highly Ordered Conductive Porous Framework - Xiao, Xiaofen; Fang, Zhengsong; Yu, Dingshan (Frontiers in Materials, 2019)
MnO2 has been widely used as an alternative candidate for oxygen reduction reaction owing to its abundance, low cost, and environmental compatibility. However, bulk MnO2 as electrocatalysts is still suffering from serious active sites agglomeration and poor conductivity, resulting in low utilization of catalysts and sluggish reaction kinetics. In view of this, we fabricated a 3D highly ordered porous MnO2@Ni-pc nanocomposite and significantly enhance ORR performance of MnO2 with high onset potential of 1.04 V and half-wave potential of 0.89 V as well as a large limiting current density of 4.07 mA cm−2, being even comparable to the commercial Pt/C. This nano-engineering technique is suitable for various catalysts that can be attached onto the 3D highly ordered porous framework, which provides new opportunities in designing electrode structures to boost the performance of bulk materials.